Assessing the efficacy of writing centres: a review of selected evaluation studies - Tan, Bee Hoon (Universiti Putra Malaysia Press, 2009)
Writing practitioners, especially those in North America, have been reporting positive results from using writing centres in supporting students’ writing processes. Yet the question of how efficacious a writing centre can be is seldom seriously considered. In view of this gap, this paper attempts to examine several important evaluation studies of writing centre efficacy from the limited literature of empirical research, and presents evidence from both qualitative and quantitative measurements. While the formal qualitative studies affirmed the effectiveness of writing centre in reducing students’ writing apprehension and promoting positive affects to writing, the quantitative studies found that writing centre tutorials improved students’ writing competence and overall grades. Nevertheless, further research is required to establish the relationship between students’ satisfaction levels and the number of writing centre tutorials they received.